From Strategy to Engagement: The Impact of the Scientific Approach on English Reading Performance in Indonesian Junior Secondary Schools - Bachtiar (CV. Creative Tugu Pena, 2025)
Grounded in constructivist and engagement theories, the scientific approach to language learning emphasizes observation, inquiry, and application as central processes that foster deep comprehension and active participation. Within the context of English language reading, this study sought to investigate the extent to which the scientific approach enhances students’ reading comprehension and engagement. Employing a quasi-experimental design, the research involved an experimental group that received instruction through the scientific approach and a control group that received conventional instruction. Data was collected through pre- and post-tests, a structured engagement questionnaire, and semi-structured interviews, which were analyzed both quantitatively and qualitatively. The findings revealed that while the between-group differences were not statistically significant, students in the experimental group demonstrated notable improvements in reading comprehension scores, rising from a mean of 76.17 to 84.83. Moreover, nearly 70% of participants reported high to highest engagement, supported by qualitative evidence of increased motivation, active participation, and strategy use. These results underscore the pedagogical value of integrating scientific approach principles into English instruction to enhance comprehension and sustain learner engagement, though further large-scale and longitudinal studies are recommended.